Did Freud misinterpret reported memories of sexual abuse as fantasies? - Powell, Russell A.; Boer, Douglas P. (My University, 1995)
Argues that Freud may have misinterpreted real memories of sexual abuse as imaginary after his abandonment of the seduction theory. Certain theoretical statements by Freud, as well as his advice to Jung concerning a 6-yr-old girl who had accused her foster-father of sexual abuse, indicate that he may have been significantly biased toward interpreting certain types of incest allegations as fantasies. Increased awareness of Freud's biases, both in his early tendency to pressure patients into believing that they were victims of abuse and in his later tendency to regard certain types of incest allegations as unreal, may contribute to a more objective approach to the diagnosis and treatment of sexual abuse in the future.
Keywords: Freud (Sigmund); imagination; memory; sexual abuse; victimization; adolescent; adult; child; child abuse, sexual; fantasy; female; Freudian theory; humans; incest; male; mental recall; psychoanalytic interpretation; psychoanalytic therapy; repression, psychology; truth disclosure